Integration of priority population, health and nutrition interventions into health systems: systematic review - Adeyi Olusoji; Ohiri Kelechi; Secci Federica V; de Jongh Thyra E; Atun Rifat; Car Josip (BMC, 2011)
Abstract Background Objective of the study was to assess the effects of strategies to integrate targeted priority population, health and nutrition interventions into health systems on patient health outcomes and health system effectiveness and thus to compare integrated and non-integrated health programmes. Methods Systematic review using Cochrane methodology of analysing randomised trials, controlled before-and-after and interrupted time series studies. We defined specific strategies to search PubMed, CENTRAL and the Cochrane Effective Practice and Organisation of Care Group register, considered studies published from January 1998 until September 2008, and tracked references and citations. Two reviewers independently agreed on eligibility, with an additional arbiter as needed, and extracted information on outcomes: primary (improved health, financial protection, and user satisfaction) and secondary (improved population coverage, access to health services, efficiency, and quality) using standardised, pre-piloted forms. Two reviewers in the final stage of selection jointly assessed quality of all selected studies using the GRADE criteria. Results Of 8,274 citations identified 12 studies met inclusion criteria. Four studies compared the benefits of Integrated Management of Childhood Illnesses in Tanzania and Bangladesh, showing improved care management and higher utilisation of health facilities at no additional cost. Eight studies focused on integrated delivery of mental health and substance abuse services in the United Kingdom and United States of America. Integrated service delivery resulted in better clinical outcomes and greater reduction of substance abuse in specific sub-groups of patients, with no significant difference found overall. Quality of care, patient satisfaction, and treatment engagement were higher in integrated delivery models. Conclusions Targeted priority population health interventions we identified led to improved health outcomes, quality of care, patient satisfaction and access to care. Limited evidence with inconsistent findings across varied interventions in different settings means no general conclusions can be drawn on the benefits or disadvantages of integrated service delivery.